2014
DOI: 10.1002/2013jb010776
|View full text |Cite
|
Sign up to set email alerts
|

Present‐day deformation of northern Pakistan from Salt Ranges to Karakorum Ranges

Abstract: Episodic GPS measurements are used to quantify the present-day velocity field in the northwestern Himalaya from the southern Pamir to the Himalayan foreland. We report large postseismic displacements following the 2005 Kashmir earthquake and several mm/yr thrusting of the central segment of the Salt Ranges and Potwar Plateau over the foreland, westward thrusting of Nanga Parbat above the Kohistan Plateau, and~12 mm/yr SSE velocities of the Karakorum Ranges and of the Deosai and Kohistan Plateaus relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 50 publications
5
34
1
Order By: Relevance
“…The BBF is interpreted to merge at a depth in the roof thrust above the HHS. The location of the roof thrust at a depth of about 15 km in the hinterland coincides with the interpretation of the earthquake hypocenter and ductile afterslip along the flat part of BBF (Jouanne et al 2011(Jouanne et al , 2014 and gravity modeling (Khan and Ali 1997). The floor thrust is located at the base of the HHS.…”
Section: Structural Cross Sectionsupporting
confidence: 78%
See 2 more Smart Citations
“…The BBF is interpreted to merge at a depth in the roof thrust above the HHS. The location of the roof thrust at a depth of about 15 km in the hinterland coincides with the interpretation of the earthquake hypocenter and ductile afterslip along the flat part of BBF (Jouanne et al 2011(Jouanne et al , 2014 and gravity modeling (Khan and Ali 1997). The floor thrust is located at the base of the HHS.…”
Section: Structural Cross Sectionsupporting
confidence: 78%
“…Khan and Ali (1997) interpreted the MBT as a fault that penetrates to a depth of about 20 km along the NE side of the HKS. Jouanne et al (2014) reported a post-seismic ductile slip at a depth of about 15 km along BBF. The Moho is modeled at a depth of about 65 km in the hinterland of the Himalayas in north Pakistan (Duroy et al 1989;Khan and Ali 1997;Khan et al 2010).…”
Section: Structural Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although coverage is sparse in some parts of Tibet (Figure 1), GPS velocities, however, can be used to infer strain rates across the region, and we exploit them here to make such a comparison. confidence ellipses), including some data from other published sources, e.g., Tien Shan [Zubovich et al, 2010], Pamir and Hindu Kush regions [Ischuk et al, 2013;Mohadjer et al, 2010], Himalaya [Ader et al, 2012;Banerjee and Bürgmann, 2002;Banerjee et al, 2008;Bettinelli et al, 2006;Jouanne et al, 2014;Schiffman et al, 2013], and Myanmar [Devachandra et al, 2014;Gahalaut et al, 2013;Maurin et al, 2010]. The India-Eurasia rotation pole for an India plate reference frame with respect to Eurasia lies at 27.46°N…”
Section: Introductionmentioning
confidence: 99%
“…1). Recent geodetic studies have suggested that the Kalabagh fault is still active, with an average slip rate of around 5.3 mm/year (Chen & Khan, 2010;Jouanne et al, 2014). Moreover, a GPS study indicates that the Potwar Plateau is moving southward at rate of 5 mm/year (Jouanne et al, 2014).…”
Section: Introduction and Tectonic Settingmentioning
confidence: 99%